Monte Carlo simulations of amphiphiles : a systematic study - Kenward, Martin, 1975- (2001)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2001. Physics and Physical Oceanography Bibliography: leaves 122-137 The study of amphiphilic molecules and their behaviour in solution is encompassed in a broad array of disciplines. The utility and prevalence of these molecules in our everyday lives and in a wide array of practical applications have stimulated a great deal of effort to understand their properties. Moreover the interesting behaviour of amphiphilic molecules in solution has received much attention. One specific example is the formation of macro-molecular aggregates composed of many amphiphilic molecules and often referred to as micelles. -- In this thesis we examine systems of self-assembling amphiphilic molecules using Monte Carlo simulations. Aggregates of amphiphilic molecules in solution are not mono-disperse; there is a broad distribution of aggregate sizes. This distribution has characteristic properties and contains information about the free energy of the system and other properties. Qualitative comparisons are made between a predicted form of the aggregate size distribution, a model for the free energy of aggregates and the results from the simulations. Direct comparisons between the Monte Carlo results and results from experiment are not carried out. -- We carry out a systematic examination of the aggregation of amphiphiles. This examination is based on a variation of the molecular weight, the temperature (or so-called reduced interaction parameters) and various other parameters. An examination of the aggregate composition, morphology and the critical micelle concentration is also carried out.